An Analysis of Lexical Cohesion in the "Alice in Wonderland" Novel by Lewis Carroll - Kuspiyah, Hastuti Retno; Nova, Nisa Arinda; Rohmah, Ainur (ENJEL: English Journal of Education and Literature, 2024)
The title of this study is An Analysis of Lexical Cohesion in the Novel Alice in Wonderland. The purpose of this study is to explore the type and amount of lexical cohesion in Lewis Carroll's novel Alice in Wonderland. The method that the writer used is descriptive qualitative method. The technique of data collection used in this study involves several steps such as reading the novel searching for lexical cohesion in the novel and make a note of lexical cohesion in the novel. The source of data for this study is Lewis Carroll's novel Alice in Wonderland. The lexical cohesion that is the focus of this research are repetition, synonym, superordinate, and general noun. Based on the results of data analysis, it was found as much as 103 data. They were 64 findings (62%) of repetition, 11 findings (10,5%) of synonym, 24 findings (23,5%) of superordinate and 4 findings (4%) of general noun. From the finding above it can be seen that the most domineering is Repetition with 64 data findings with a percentage of 62 %.